Female Crime and Delinquency in Portugal In and Out of the Criminal Justice System (Springer International Publishing, 2018)
This book compiles research on female crime and delinquency in Portugal in order to critically and reflectively explore interdisciplinary views on the link between gender, crime and delinquency. Contributions are organized into two main parts, with Part I dedicated to the relationship between women and crime, and Part II focused on female juvenile delinquency. Through the exploration of girls' and women's relationships with delinquency and crime, as well as with the justice system, this original and compelling collection highlights the heterogeneity of girls' and women's experiences, whilst also underlining the convergences and divergences between them. Ultimately, Gomes and Duarte argue that understanding how women and girls explain their offending behaviours and how they relate to the criminal justice system is of the utmost importance for reforming social and legal policies. As such, this book will be of value not only for students, researchers and professionals of the social, behavioural and criminal sciences, but also for policy-makers seeking to provide greater efficiency in preventing crime and delinquency.